Human-Water Monitor Conflicts in Indonesia: Spatial Patterns and Mitigation Alternatives - Farid Rifaie; Evy Arida; Noor Laina Maireda; Kamal Muftie Yafi (The Ethnobiological Society of Indonesia, 2023)
The exponential growth of the human population in the last few decades has had an impact on the exponential increase of agricultural land. One of the consequences arising from the forest land conversions is the increasing number of conflicts between wildlife and humans. Although human-wildlife conflicts are also common in Indonesia, efforts to inventory and monitor the types of conflicts and their distribution are still limited. Mammals and birds are the only two groups of wildlife that are widely studied. This study tries to collect data on the incidences of human-water monitor interactions that are often reported by online news. The collection of news from online media (web scraping) is done automatically using the python package GoogleNews. The collected news articles were stored in a spreadsheet format and processed to obtain information on the location and type of conflict. The scraping process collected 1,838 news articles related to water monitors that represented 189 cases of human-water monitor conflicts. However, there were only 172 conflict cases that had detailed information of the location. The spatial autocorrelation analysis revealed a significant clustering pattern in the Jakarta Metropolitan area. The most common incident was water monitors coming into a house or neighborhood. The reports also uncovered that at least eight people lost their lives and seven water monitors were killed or sold. In addition, there were about 81 captured water monitors with uncertain or untraceable status. Commercially harvesting water monitors, particularly in highly urbanized cities, can be a reasonable solution for this problem.